2022
DOI: 10.1186/s12920-022-01232-w
|View full text |Cite
|
Sign up to set email alerts
|

FAM201A, a long noncoding RNA potentially associated with atrial fibrillation identified by ceRNA network analyses and WGCNA

Abstract: Background Being the most common arrhythmia in clinic, atrial fibrillation (AF) causes various comorbidities to patients such as heart failure and stroke. LncRNAs were reported involved in pathogenesis of AF, yet, little is known about AF-associated lncRNAs. The present study aims to explore lncRNAs associated with AF susceptibility based on competing endogenous RNA (ceRNA) network analysis and weighted gene co-expression network analysis (WGCNA). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The expression of lncRNA is highly tissue- and cell type-specific, and the mechanisms of lncRNAs acting as ceRNAs in human AF remain unclear. Chen et al constructed an AF-related ceRNA network by identifying lncRNAs from the GSE41177 and GSE79768 datasets, and they reported that lncRNA FAM201A acts as a miRNA sponge of miR-33a-3p to upregulate the expression of the Rac family small GTPase 3 (RAC3) target gene, thereby participating in the regulation of AF susceptibility ( 24 ). In the present study, we found that the target genes of the lncRNA network were mainly involved in the adaptive immune response, inflammatory response, T/B cell receptor signaling pathway, and calcium signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNA is highly tissue- and cell type-specific, and the mechanisms of lncRNAs acting as ceRNAs in human AF remain unclear. Chen et al constructed an AF-related ceRNA network by identifying lncRNAs from the GSE41177 and GSE79768 datasets, and they reported that lncRNA FAM201A acts as a miRNA sponge of miR-33a-3p to upregulate the expression of the Rac family small GTPase 3 (RAC3) target gene, thereby participating in the regulation of AF susceptibility ( 24 ). In the present study, we found that the target genes of the lncRNA network were mainly involved in the adaptive immune response, inflammatory response, T/B cell receptor signaling pathway, and calcium signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from its role in cancers, a decrease in FAM201A expression has been linked to osteonecrosis of the femoral head [ 32 ]. Recently, Chen et al revealed that FAM201A was associated with an increased susceptibility to atrial fibrillation through ceRNA network analysis [ 33 ]. This study indicated that the down-regulation of FAM201A could potentially be used as a predictive marker for atrial fibrillation susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FAM201A (the family with sequence similarity 201 member A) is an RNA gene affiliated with the lncRNA class. The decrease in lncRNA FAM201A expression is related to mRNA RAC3 downregulation favoring autophagy, which could lead to a decrease in the L-type calcium channel expression and current, shortening the action potential duration [ 32 ]. Likewise, cardiac apoptosis-related lncRNA competitively binds to miR-539, preventing the miR-539-dependent downregulation of the protein PHB2.…”
Section: Diseasome and Non-coding Rnas In Af Pathogenesismentioning
confidence: 99%